Component mode synthesis methods for a body-in-white noise and vibration analysis. (February 2017) - Vizzini, Simone; Olsson, Magnus; Scattina, Alessandro
In this work the dynamic substructuring approach was applied to a noise, vibration and harshness problem within the automotive engineering field. In particular, a noise, vibration and harshness analysis was carried out on the body-in-white structure of a passenger car. The work focuses on the theory of component mode synthesis. Two component mode synthesis reduction methods, namely the Craig–Bampton method and the Craig–Chang method, were applied to the body-in-white structure of the Volvo V40. The influences of various parameters were investigated. In particular, the effect of the reduction basis on the response accuracy and on the reduction time was studied. Moreover, the effects of the connection properties between different parts of the model were examined. The simulation times of the reduced models and of the full finite element model were compared. The results showed that the Craig–Chang method performs better when the modes are retained for up to one and a half times the maximum frequency response studied. Additionally, the Craig–Chang method gives a very accurate representation of the system dynamics even when connections with a low stiffness are used. Finally, it is possible to reduce the simulation time by up to 90% if component mode synthesis methods are used instead of the full finite element model.